Entrepreneurial dispositions, time horizons, and context: subtleties that shape entrepreneurial intentions. Issue 2 (4th May 2021) - Qingqing, Bi; Collins, Jamie; Ranabahu, Nadeera
ABSTRACT: Entrepreneurial intention is a critical concept in the 'pre-start' stage of new venture creation. In this study, we differentiate between entrepreneurial intentions in general and in the near future and examined the personal dispositions to entrepreneurship and contextual factors which might influence entrepreneurial intentions. We develop our research model by integrating the direct and interaction effects between these factors. We employ a large-scale cross-country dataset, Gallup World Poll, to empirically test our research framework. The results indicate that both personal dispositions and contextual factors have a direct significant influence on entrepreneurial intentions in general and in the near future. The interaction effect only has a significant influence on entrepreneurial intentions in the near future. This study contributes to the entrepreneurship literature by enriching our understanding of different subtleties that influence entrepreneurial intentions and highlighting the importance of the interactions between personal dispositions and contextual factors in shaping entrepreneurial intentions.